Informational content of short interest (EBES 2011) - Mohamad, Azhar (2011)
This paper examines the information content of short interest by examining whether firms that experience significant increase in short interest subsequently experience negative returns. Using the UK daily short interest data from the period of September 2003 to April 2010, we find a significant cumulative average abnormal return post-publication of short interest data. We also find the larger the increase in short interest, the more negative is the abnormal returns. The results indicate informational content of short interest which is consistent with Diamond and Verrecchia (1987) hypotheses.